2006
DOI: 10.1111/j.1540-8159.2006.00294.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prophylaxis with a Single Dose of Cefazolin During Pacemaker Implantation: Incidence of Long‐Term Infective Complications

Abstract: Our data indicate the safety and efficacy of a single, intravenous 2 g dose of cefazolin in preventing infective complications related to pacemaker implantation or replacement. No clinical or procedural variable predicted the occurrence of long-term infective complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 17 publications
1
34
0
2
Order By: Relevance
“…Implantation of a new system compared with partial or complete system replacement and use of periprocedural antimicrobial prophylaxis were both associated with a lower risk of infection (Klug et al, 2007). There is evidence that perioperative antimicrobial prophylaxis is associated with a reduction in CIED infections (Bertaglia et al, 2006;Da Costa et al, 1998b;de Oliveira et al, 2009). Other small studies suggest that pectoral transvenous device placement is associated with significantly lower rates of CIED infection than those implanted abdominally or by thoracotomy.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Implantation of a new system compared with partial or complete system replacement and use of periprocedural antimicrobial prophylaxis were both associated with a lower risk of infection (Klug et al, 2007). There is evidence that perioperative antimicrobial prophylaxis is associated with a reduction in CIED infections (Bertaglia et al, 2006;Da Costa et al, 1998b;de Oliveira et al, 2009). Other small studies suggest that pectoral transvenous device placement is associated with significantly lower rates of CIED infection than those implanted abdominally or by thoracotomy.…”
Section: Risk Factorsmentioning
confidence: 99%
“…A following observational study was performed to assess the safety and long-term efficacy of a simple scheme of antibiotic prophylaxis, and to identify the predictors of long-term infective complications in patients undergoing pacemaker implantation or replacement. This study showed the efficacy of a single dose of cefazolin in preventing infective complications (Bertaglia et al, 2006). Finally a prospective, randomized, double-blinded, placebo-controlled trial was developed to determine whether prophylactic antibiotic administration reduces the incidence of infection related to device implantation was.…”
Section: Pharmacological Strategiesmentioning
confidence: 99%
“…During long-term follow-up, major infectious complications were observed in six patients (0.7 %). 37 A randomised controlled prospective study comparing CIED implantation with or without cefazolin prophylaxis was undertaken but prematurely discontinued after reaching 65 % of the planned enrolment, due to appearance of a significant difference in favour of the antibiotic arm (0.63 versus 3.28 infected patients, p=0.016). 38 Although vancomycin is not generally recommended, it may be considered as an alternative at centres where oxacillin resistance is high.…”
Section: Treatment and Preventionmentioning
confidence: 99%
“…13,17,18 On the other hand, antibiotic prophylaxis seems to reduce the risk of infection. 19,20 Making the Diagnosis Pathogenesis CIED infections can be broadly categorized as follows:…”
Section: Scope Of the Problemmentioning
confidence: 99%